Effects of ethanol extract of Zea mays hairs on liver function tests in alcohol fed rats - Sim, Lee, Ling (Universiti Sains Malaysia, 2006)
The ethanol extract of Zea mays hairs was screened for the effects on liver functions in alcohol fed rats. 30 male Sprague dawley rats were divided into six groups with five rats in each group. There were control group, 50mglkg body weight extract group, alcohol group, 50mglkg body weight extract+ alcohol group, 100 mglkg body weight extract group and 100 mg/kg body weight extract + alcohol group. All six groups were treated for 14 days. The ethanol extract of Zea mays hairs increased total protein and globulin significantly in high dose (IOOmg). 3ml of 30% alcohol also increased these two parameters (increase in total protein was non significant). The extract with alcohol, increased the total protein and globulin more than the extract alone. Albumin also showed non significant increase in 50mg, 1 OOmg extract and 50mg extract with alcohol. But alcohol alone decreased albumin significantly. As filr as the liver enzymes are concerned, there was no significant change in alkaline phosphatase (ALP), aspartate aminotransferase (AST) and alanine aminotransferase ( AL T). The results showed that the extract increased protein synthesis in the liver and did not cause any damage to the liver. 3 ml of30% alcohol when given for 14 days did not cause any adverse effect on protein synthesis and also did not cause any affect to the enzymatic functions of the liver. xi